Evaluation of segmented non-target data acquisition (SWATH/vDIA) in a QToF and QOrbitrap for pesticide residue analysis. Issue 15 (3rd April 2020) - Rajski, Łukasz; Beraza, Iciar; Gómez Ramos, María José; Ferrer, Carmen; Fernández-Alba, Amadeo R.
Abstract : Two high-resolution instruments (a QToF and a QOrbitrap) were used to evaluate a segmented non-target MS2 (SWATH/vDIA) acquisition for pesticide residue analysis. Abstract : Two high-resolution instruments (a QToF and a QOrbitrap) were used to evaluate a segmented non-target MS2 (SWATH/vDIA) acquisition for pesticide residue analysis. Three matrices (tomato, orange, and leek) and 163 pesticides were used for this study. Samples were analysed by use of 1, 5, 8, and 20 mass windows and the last one was used only in the QToF. The objectives of the evaluation were: the number of detected fragment ions, mass accuracy, ion ratio, and sensitivity. Obtained results showed a positive influence of the mass windows on the detection of the fragment ions, ion ratio stability and mass accuracy with no effect on the sensitivity of the analysis. The experiments revealed the importance of the size of the mass windows selected. Therefore, the use of variable mass windows optimizing the size is necessary in case of limitations of the scan speed. Nevertheless, the contemporary instrumentation still cannot achieve a high number of very narrow mass windows (<10 Da) what is necessary for the optimal selectivity.